Assessing service quality of online bill payment system using extended SERVQUAL model (SERVQUAL-Butterfly model): A case study of Dhaka electric supply company limited (DESCO), Bangladesh - Mohammad Anisur Rahman; Xu Qi; Abu Naser Mohammad Saif; Ismail Bin Ibrahim; Rabeya Sultana (Cogent Business & Management, 2017)
The aim of this paper is to assess the service quality of Dhaka Electric Supply Company Limited's (DESCO) online bill payment system using extended SERVQUAL model termed as SERVQUAL-Butterfly Model that integrates customer expectation and perception of actual service quality, customer satisfaction, and loyalty. Using random sampling method, primary data were collected from a total of 300 customers from three operating zones of DESCO. The data were analyzed through PLS-SEM second-order hierarchical modeling approach and Importance-Performance Map Analysis (IPMA). We found that expectation on service quality has no effect on customer satisfaction; however, it influences the formation of perception about the actual quality of service. Customer satisfaction is significantly influenced by the perception of actual service quality and customer satisfaction significantly helps to make the customer loyal. For DESCO, empathy found to be a powerful indicator of both expectation and actual service quality and perception of actual service found to be the single most important factor for customer satisfaction. Future researchers can use this SERVQUAL-Butterfly Model that eliminates inherent limitations of original SERVQUAL model and augment it according to their specific industry, context, and culture.
Keywords: 650